2018
DOI: 10.1080/02626667.2018.1469757
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and evaluation of potential climate change impact on monsoon flows using machine learning technique over Wainganga River basin, India

Abstract: In this study, classification-and regression-based statistical downscaling is used to project the monthly monsoon streamflow over the Wainganga basin, India, using 40 global climate model (GCM) outputs and four representative concentration pathways (RCP) scenarios. Support vector machine (SVM) and relevance vector machine (RVM) are considered to perform downscaling. The RVM outperforms SVM and is used to simulate future projections of monsoon flows for different periods. In addition, variability in water avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 90 publications
1
23
0
Order By: Relevance
“…We applied the train() function from the caret package in R (http://topepo.github.io/caret/index.html) to fit linear regression with backward selection, which starts with all predictors in the model, iteratively removes the least contributive predictors until all predictors are statistically significant (Kassambara, 2018). The RVM method was chosen because it was applied in several previous direct downscaling studies and always showed good model performance (Ghosh and Mujumdar, 2008; Okkan and Inan, 2015; Das and Nanduri, 2018). Both models used 10‐fold cross‐validation to estimate the mean squared error and to select the best model based on the smallest error.…”
Section: Methods and Datamentioning
confidence: 99%
See 3 more Smart Citations
“…We applied the train() function from the caret package in R (http://topepo.github.io/caret/index.html) to fit linear regression with backward selection, which starts with all predictors in the model, iteratively removes the least contributive predictors until all predictors are statistically significant (Kassambara, 2018). The RVM method was chosen because it was applied in several previous direct downscaling studies and always showed good model performance (Ghosh and Mujumdar, 2008; Okkan and Inan, 2015; Das and Nanduri, 2018). Both models used 10‐fold cross‐validation to estimate the mean squared error and to select the best model based on the smallest error.…”
Section: Methods and Datamentioning
confidence: 99%
“…By directly linking GCM outputs and hydrological variables, uncertainty introduced by different RCMs, post‐processing methods and hydrological models can, in principle, be avoided. In addition, such a method is simple and computationally efficient, so it can be easily applied to a full ensemble of GCM outputs to account for the uncertainty contributed by the GCMs (Das and Nanduri, 2018). However, the direct downscaling method has also been criticized for its over‐simplification of the hydrological cycle and its lack of water stores and transfers within the soils and groundwater of a catchment (Xu, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The elevation of the catchment varies from 144 to 1036 m above sea level [53]. Agricultural lands and forests are the major land use over the catchment [54]. Figure 1 represents the location of the catchment in India along with the observed monsoonal average rainfall during the study period.…”
Section: Study Areamentioning
confidence: 99%